Gender differences in leadership behaviors of female coaches and their leadership effectiveness - Yu, S.; Wang, H. (International Journal of Sports Science & Coaching, 2025)
The purpose of this study is to explore the gender differences in the leadership behaviors of female coaches within the context of China's national conditions and cultural background, and to examine their impact on athletes` followership. Additionally, the study investigates the influence mechanism after introducing the organizational variable of the mentor-mentee relationship, as well as the moderating role of work goals as a dynamic variable in the overall influence mechanism. The research method involved administering a scale-based test to 1,071 Chinese athletes from basketball, volleyball, and soccer teams, including those from professional teams, youth teams, and university high-level teams. Regression analysis, factor analysis, and structural equation modeling were used to process the data. The research findings are as follows: (1) Compared to male coaches, the decisive and dominant behavior and supervision and inspection behavior are prominent features of Chinese female coaches` leadership, and both significantly predict athletes` followership, demonstrating strong leadership effectiveness. The mentor-mentee relationship and team work goals have mediating and moderating effects, respectively, on the leadership effectiveness of female coaches. (2) Supervision and inspection behavior can influence athletes` followership through its impact on the mentor-mentee relationship. Work goals negatively moderate the relationship between decisive behavior and athletes` followership, but work goals have a significantly positive moderating effect on the influence mechanism of female coaches` supervision and inspection behavior on athletes` followership when the mentor-mentee relationship is considered as a mediating variable. Specifically, when the mentor-mentee relationship is good, higher work goals lead to a stronger moderating effect.